Impact of Hypothermic Temperature Control on Plasma and Soft Tissue Pharmacokinetics of Penicillin/Beta-Lactamase Inhibitor Combinations in Patients Resuscitated After Cardiac Arrest - Stommel, Alexandra-Maria; Matzneller, Peter; al Jalali, Valentin; Wulkersdorfer, Beatrix; Lackner, Edith; Mueller, Matthias; Dorn, Christoph; Holzer, Michael; Zeitlinger, Markus (Clinical pharmacokinetics, 2025)
Penicillin/beta-lactamase inhibitors are often used to treat aspiration pneumonia in patients resuscitated after cardiac arrest (CA). The impact of hypothermic temperature control on the pharmacokinetics of amoxicillin/clavulanate (AMO/CLAV) and ampicillin/sulbactam (AMP/SULB) has not been studied. Our objective was to evaluate the effects of hypothermic temperature control on the plasma and soft tissue pharmacokinetics of AMO/CLAV and AMP/SULB, including pulmonary concentrations of AMP/SULB, in patients resuscitated after CA. This prospective clinical study involved ten adult patients after CA receiving either AMO/CLAV 2 g/0.2 g or AMP/SULB 2 g/1 g intravenously every 8 h. Patients underwent hypothermic temperature control (33 ± 1 °C) for 24 h, followed by normothermia. Plasma, urine, muscle, and subcutaneous pharmacokinetics were measured and plasma protein-binding assessed for each subject. Microdialysis determined unbound drug concentrations in soft tissues. The pulmonary concentration of AMP/SULB was analyzed in the epithelial lining fluid. No significant differences in plasma pharmacokinetics or renal excretion of AMO/CLAV and AMP/SULB were observed between the two temperature conditions. Soft tissue concentrations showed no consistent trend. Pharmacokinetic/pharmacodynamic targets (time that the unbound plasma concentrations were above the minimal inhibitory concentration [MIC] for MIC up to 8 mg/L) were met but not for 16 mg/L. Pulmonary concentrations of AMP/SULB in the epithelial lining fluid showed no clear trend. This study indicates that hypothermic temperature control does not significantly affect plasma concentrations, soft tissue concentrations, or renal excretion of AMO/CLAV and AMP/SULB in patients resuscitated after CA. However, pulmonary concentrations of AMP/SULB exhibited interindividual variability.